Stereotipe Gender dalam Serial Drama Daughter of Lupin (2019) - Fairuzzahra, Nabila Vina (UI Scholars Hub, 2021)
Stereotypes shown by the media have influenced how society constructs their perspective on gender. Japanese television program that contained gender stereotypes is Daughter of Lupin (2019) drama series. This research aims to identify and explain gender stereotypes shown in Daughter of Lupin through the characterization of Mikumo Hana. This research is qualitative descriptive and it uses semiotic approach by Roland Barthes to analyze data. The result shows that Daughter of Lupin drama series has two types of gender stereotypes, which are traditional gender stereotypes and shifted gender stereotypes. It indicates that Daughter of Lupin is not fully breaking down the traditional gender stereotypes, but is also keeping some of them.